The Effect of Practicum-Based Learning on Elementary Students’ Achievement in Magnetism - Afifah Sellen Dila; Siti Shalihah; Khairunnisa Khairunnisa; Mila Hasanah (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study empirically examines the instructional effectiveness of the practicum method on the learning achievement of Grade 5 students in Integrated Science and Social Studies (IPAS), with a focus on the topic of magnetism at MIS Muhammadiyah 3 Al-Furqan. Conventional IPAS instruction remains largely teacher-centered, limiting students' understanding of abstract scientific concepts. To address this issue, the study implemented a practicum-based learning approach. A quantitative quasi-experimental design with a nonequivalent control group was employed, involving 52 fifth-grade students divided into an experimental class and a control class. Learning outcomes were measured using pretest and posttest instruments and analyzed using an independent samples t-test. The results showed that the experimental class achieved significantly higher posttest scores (M = 77.62) than the control class (M = 66.19) (p = 0.004). The effect size analysis revealed a significant practical effect of the practicum method on learning achievement (Cohen's d = 0.84), indicating strong pedagogical significance. This study provides empirical evidence supporting the integration of practicum-based learning to enhance elementary IPAS instruction within the madrasah ibtidaiyah context.